Visitantes florais em híbridos de canola (Brassica napus L.) no cerrado mineiro - Fuzaro, Leandro (2017)
The canola crop (Brassica napus L.) is one of the most important oilseeds in the world agriculture and one of the main sources of edible vegetable oil, besides being an important source of renewable energy, for its use in the biodiesel production. Although canola is considered a self-sustaining crop, is extremely attractive to bees and can be pollinated by them during collection of pollen and/or nectar, resulting in heavier silica with a larger number of seeds. Due to the few studies about the diversity of pollinators and the effect of pollination services on canola productivity in Cerrado Mineiro region, the objective was to identify the main visitors of canola flowers; determining, in two commercial hybrids of canola - Hyola 61 and Hyola 433, which are the main pollinators of the crop and verify if the productivity increases when occurs pollination by bees . The studies were conducted at the Experimental Farm Água Limpa of the Federal University of Uberlândia, located at 19º05'48 ''S, 48º21'05''W and at an altitude of approximately 800 m. A completely randomized experimental plot design was used in the factorial scheme with two hybrids and two treatments of pollination (open and closed to visitation of insects), and 10 replications, totalizing 20 plots. The survey of floral visitors occurred during May and June of 2016, during 10 days. The faunistic analyzes of the collected species were performed based on frequency, constancy, dominance, richness and diversity indexes. To evaluate the pollination by bees in canola seeds production, an experiment was carried out to exclude floral visitors, comparing the productivity of the silique formed by open and closed flowers to insect visitation, in both hybrids. A total of 2,294 individuals belonging to 19 species of bees of two families (Apidae and Halictidae) were collected. The richness and diversity among the hybrids were similar and the species Apis mellifera Linnaeus, 1758 (Hymenoptera: Apidae), Paratrigona lineata Lepeletier, 1836 (Hymenoptera: Apidae) and Trigona spinipes Fabricius, 1793 (Hymenoptera: Apidae) were the most abundant and constant in the crops, being considered effectives canola pollinators. In addition, the free visitation of insects resulted in 25% and 18.8% heavier siliques and 22.5% and 20.6% more seeds in Hyola 61 and Hyola 433, respectively. Despite being a still new crop in the Minas Gerais triangle region, canola was receptive to local insects, attracting a large number of floral visitors, with three species (two native ones) considered effective pollinators. Increases in productivity highlight the importance of protecting these insects and the conservation of natural areas close to crops, so that they provide subsidies for the maintenance of populations and the service of pollination provided by them in canola crops.